Interprofessional Faculty Development on Health Disparities: Engineering a Crossover "Jigsaw" Journal Club - Jessica T. Servey; Gayle Haischer-Rollo (MDPI AG, 2024)
Medical education acknowledges our need to teach our physicians about "social determinants of health" and "health care disparities". However, educators often lack actionable training to address this need. We describe a faculty development activity, a health disparities journal club, using the jigsaw strategy with the intent of increasing awareness, encouraging self-directed learning, and inspiring future teaching of the subject to health professional learners. We completed six workshops at six individual hospitals, with 95 total attendees in medicine and numerous other health professions. Our evaluation asked trainees to: report the number of journal articles about health disparities they had read, excluding the assigned journal club articles, in the past 12 months, and to predict future plans for reading about health disparities. In total, 28.9% responded they had "never read" a prior article on health or healthcare disparities, while 54.2% responded "1-5 articles". Many (60%) reported they would continue to investigate this topic. Our experience has demonstrated the utility and positive impact of a "flipped classroom" jigsaw method, showing it can be used successfully in Inter-Professional (IPE) Faculty Development to increase active exposure and discussion of the content. Additionally, this method promotes individual reflection and enhances continued collective engagement.